If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(5 + -7) * 3y(y + -4) = 7x + 45 Combine like terms: 5 + -7 = -2 2x(-2) * 3y(y + -4) = 7x + 45 Reorder the terms: 2x * -2 * 3y(-4 + y) = 7x + 45 Reorder the terms for easier multiplication: 2 * -2 * 3x * y(-4 + y) = 7x + 45 Multiply 2 * -2 -4 * 3x * y(-4 + y) = 7x + 45 Multiply -4 * 3 -12x * y(-4 + y) = 7x + 45 Multiply x * y -12xy(-4 + y) = 7x + 45 (-4 * -12xy + y * -12xy) = 7x + 45 (48xy + -12xy2) = 7x + 45 Reorder the terms: 48xy + -12xy2 = 45 + 7x Solving 48xy + -12xy2 = 45 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 48xy + -7x + -12xy2 = 45 + 7x + -7x Reorder the terms: -7x + 48xy + -12xy2 = 45 + 7x + -7x Combine like terms: 7x + -7x = 0 -7x + 48xy + -12xy2 = 45 + 0 -7x + 48xy + -12xy2 = 45 Reorder the terms: -45 + -7x + 48xy + -12xy2 = 45 + -45 Combine like terms: 45 + -45 = 0 -45 + -7x + 48xy + -12xy2 = 0 The solution to this equation could not be determined.
| x-5=83 | | 3x-44=45x^2 | | (Sinx-1)(2cosx-1)=0 | | 5X(7-4)+1= | | Tn=-2n+1 | | x-(6x+1)=8-(3x+3) | | (5y^2-2y-1)= | | 2x+8+70=180 | | (5y^2-2y-1)-(-y-2-y^2)= | | (5y^2-2y-1)-(-y-2-3y^2)= | | (W+9)(w+3)=0 | | x-3=-(3-x) | | (5y^2+7x+3)-(-y-2-3y^2)= | | x-3000=3(x-3000) | | (x-.57)(x+.5)=0 | | 6a+5=18 | | x+3(x-1)=(2x+3) | | 3-/2 | | 2(890)= | | 3x^2-3x+6= | | 4x+2(6+y)=13-3 | | F(x)=3cos^3x | | 6x^2-27x+60=0 | | 5(x-3)-4(x+3)=3(x-1) | | x-.3x=9000 | | x*3=9000 | | Lgx-2/8 | | 2/3×4/7 | | 12/n=24 | | 18=1.08(T/21) | | 14=-7x+56 | | -4/7=y-1/3 |